1999
DOI: 10.1039/a901149h
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tryptophan in feed samples by cyclic voltammetry and multivariate calibration methods

Abstract: A voltammetric method for the determination of tryptophan (Trp) in feed samples using multivariate calibration techniques is proposed. The multivariate data consisted of the oxidation wave of cyclic voltammograms registered from 400 to 925 mV using a graphite-methacrylate composite electrode, at which Trp was oxidized around a potential of 900 mV. The interference from other oxidizable amino acids as well as the feed sample matrix was circumvented by using multivariate calibration methods. Principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…61 Saurina et al developed an amperometric biosensor for the determination of lysine, which was added as dietary supplement to food or drugs. 31 Three different configurations of the lysine biosensor were proposed, based on rigid-conducting biocomposites (graphite-methacrylate composite electrode for the electrochemical detection of hydrogen peroxide at +1000 mV, peroxidase-modified graphite-methacrylate biocomposite electrode for the reductive electrochemical detection of oxidized peroxidase, and peroxidase-modified graphite-methacrylate biocomposite electrode for the hydroquinone-mediated detection). [61][62][63] The hydroquinone-mediated biosensor was found to work better under reductive electrochemical detection than the graphite-methacrylate electrode biosensor, by diminishing potential interferences.…”
Section: ·5 Biocomposite Electrodesmentioning
confidence: 99%
See 3 more Smart Citations
“…61 Saurina et al developed an amperometric biosensor for the determination of lysine, which was added as dietary supplement to food or drugs. 31 Three different configurations of the lysine biosensor were proposed, based on rigid-conducting biocomposites (graphite-methacrylate composite electrode for the electrochemical detection of hydrogen peroxide at +1000 mV, peroxidase-modified graphite-methacrylate biocomposite electrode for the reductive electrochemical detection of oxidized peroxidase, and peroxidase-modified graphite-methacrylate biocomposite electrode for the hydroquinone-mediated detection). [61][62][63] The hydroquinone-mediated biosensor was found to work better under reductive electrochemical detection than the graphite-methacrylate electrode biosensor, by diminishing potential interferences.…”
Section: ·5 Biocomposite Electrodesmentioning
confidence: 99%
“…It was observed that the stability of the peroxidase-modified biosensor was longer than that of the graphite-methacrylate electrode configuration. 31 After investigating possible interferences for the three configurations, the majority of amino acids were amperometrically detected at +1000 mV with the analysis of lysine for the graphite-methacrylate composite electrode. The noticeable interferences among amino acids were tryptophan, tyrosine, and cysteine acids.…”
Section: ·5 Biocomposite Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Partial least squares regression (PLS) is a chemometrics technique which has been widely used for multivariate calibration in different analytical methods such as nuclear magnetic resonance, 5 spectrophotometry, [6][7][8][9] infrared spectroscopy, 10 fluorimetry, 11 X-ray fluorescence spectrometry, 12 potentiometric titration 13 and cyclic voltammetry. 14 The artificial neural network (ANN) is another technique which is able to approximate relationship between multiple inputs and multiple outputs of a system. It has been applied successfully to the field of multivariate calibration, [15][16][17][18][19][20][21][22] but its applications are narrower than those of PLS.…”
Section: Introductionmentioning
confidence: 99%